Pembangunan Sistem Reservasi Kamar Hotel berbasis Web dengan memanfaatkan Teknologi Payment Gateway (Studi Kasus: Hotel Asri) - Muhammad Syahputra; Bayu Rahayudi; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Asri Hotel is located in Banyuwangi regency, East Java. The process of renting a room or reservation at this hotel is still written in the ledger. Customers must come in person or call-in advance to make a reservation, so there are often mistakes that harm customers and Asri Hotel. Currently, Hotel Asri also experiences problems in booking rooms due to a shortage of employees, so employees who have duties on the front end or reception are not always there. So, the step that can be taken to facilitate room reservations at Hotel Asri is to build a hotel room reservation system. The system to be built is web-based that is integrated with Midtrans's payment gateway so that guests can make room reservations and hotels in confirming room reservations. The research methodology used is the waterfall, starting from the analysis of needs in obtaining functional needs and non-functional needs of the system. Designing applications using Unified Modelling Language (UML). Functional testing of the system is performed by BlackBox testing the acquisition of 100% valid values. Non-functional testing was carried out using compatibility testing and the results of the system running in various browsers without any problems. System Usability Scale (SUS) testing was carried out on seven respondents and an average final score of 86% was obtained which based on the SUS score, the system built was accepted with the Acceptability Ranges assessment the system got an "ACCEPTABLE" score, in the Grade Scale assessment the system got a B grade and the system Adjective Ratings score got an "EXCELLENT" score.